Prosedur Penerbitan dan Pemeriksaan Faktur Pajak pada Perusahaan Self-Service Retailer Store di Era Transformasi Sistem Core Tax - Rofilla Masrukhan; Aulia Herdiani (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2025)
The transformation of Indonesia's tax administration system through the Core Tax Administration System (CTAS) presents operational challenges for taxpayers, including retail companies. This study aims to analyze the procedures for issuing and examining tax invoices, as well as the risk mitigation strategies implemented by a self-service retailer store (Company X) in Malang during this transition era. Using a qualitative method with a case study approach, data were collected through interviews, participant observation, and documentation, then analyzed using the Miles & Huberman interactive model. The results indicate that the company faces various obstacles, such as the complexity of data input that demands perfection, difficulties in classifying product codes, and system errors causing discrepancies in Tax Base (DPP) data. In response, Company X has developed systematic internal procedures, including: routine checks to detect system anomalies, creating a customer database to ensure complete information, a dual archiving system for sales notes, and designing a reference data system for product codes. These procedures have proven effective in minimizing the risk of errors, maintaining data accuracy, and ensuring compliance. This study concludes that proactive adaptation through the development of good internal procedures is key for companies to maintain smooth operations and data integrity during the digital transformation of taxation